Influence of Line Strategy Between Two Turns on Performance in Giant Slalom - Delhaye, Clément; Cross, Matthew R.; Bowen, Maximilien; Samozino, Pierre; Hintzy, Frédérique (Frontiers in Sports and Active Living, 2020)
In alpine ski racing, different line choices can drastically affect turn or sectional performance. The straight-line transition between two turns is the main phase where skiers can gain speed in a race, open their trajectory, or reduce their path length. Between two turns, the skier can foster speed increase by increasing time in the straight line inducing sharper turning phases (Z strategy). Inversely, speed can be conserved during the entire turn cycle by performing long curved turns separated by a short straight line (S strategy). This research aimed to evaluate the kinetic and kinematic specificities associated with the line strategy and to explore interactions of selected strategy with skier performance and energy dissipation. A mixed-level population of male alpine skiers (n=17), skied a timed giant-slalom course while equipped with specialized force-plates and a positional device collecting synchronized normal ground reaction force and position-time data, respectively. Time of edge switch was computed from the force signal as the period with the lowest force application on the outside ski. From positional data, turn cycles were separated into turning and straight-line phases (radius under and above 30 meters, respectively). Time length, path length in the straight line, speed amplitude and change in specific mechanical energy were computed for each turn and averaged for each skier. The path length during straight line was used to continuously characterize the line strategy within the spectrum between the Z (long straight line) to the S (short straight line) strategy Path length in the straight line is correlated with the amplitude of speed over a straight line (r=0.672, p=0.003) and relative and absolute time spent in the straight line (r=0.967, p<0.001). However, path length in straight line is not correlated to decrease of speed in the following turn (r=-0.418, p=0.390) or time without force application on outside ski (r=0.195, p=0.453). While higher-performing athletes on the course performed turns during which they dissipated less energy when normalized to entry speed (r=-0.620, p=0.008), it appears they did so with variable turn strategy approaches.